Bridging contexts in STEM professional development: validating a social validity measure across rural and nonrural educators - Crawford, Angela; Starrett, Angela (Frontiers in Education, 2025)
IntroductionThis study investigates the measurement invariance of a survey assessing perceptions of STEM professional development (PD) resources among rural and non-rural educators. Social validity theory provides the framework for examining four constructs: feasibility, usability, appropriateness, and local relevance.MethodsUsing a mixed-methods approach, we conducted multi-group confirmatory factor analysis to test for configural, metric, scalar, and strict invariance. We also conducted a qualitative thematic analysis of open-ended responses to provide contextual insights and nuance.ResultsResults indicate full measurement invariance, supporting the validity of cross-group comparisons. Quantitative analyses show that rural educators rated PD resources significantly higher in feasibility and appropriateness, while no significant differences emerged for usability or local relevance. Thematic analysis revealed that rural teachers more frequently emphasized professional learning benefits and expressed more positive sentiment toward PD resources.DiscussionThese findings highlight the importance of designing STEM PD initiatives that account for contextual differences in resource accessibility, instructional autonomy, and community relevance. Implications for policy and practice include recommendations for tailoring PD to diverse educational settings to enhance educator engagement.